Intraluminal gastric pH in chronic pancreatitis. Issue 2 (February 1995) - Bovo, P; Cataudella, G; Di Francesco, V; Vaona, B; Filippini, M; Marcori, M; Montesi, G; Rigo, L; Frulloni, L; Brunori, M P
Abstract : The aim of this study was to assess the circadian variations of intragastric pH in 28 inpatients with chronic pancreatitis (mean (SD) age 46.8 (12.4) years) and in 14 controls (45.4 (9.8)). pH Metry was performed using a monocrystalline antimony electrode placed in the body of the stomach under fluoroscopic control and connected up to a recorder (MKII Digitrapper, Synectics). The evaluation parameters, expressed as median and interquartile range, were: total period, postprandial periods (P1 and P2), interdigestive, and nocturnal phases. Patients with chronic pancreatitis were subdivided into three groups on the basis of severity of exocrine pancreatic insufficiency (secretin-caerulein test: lipase output at 60-90 min)--that is, those with severe insufficiency (chronic pancreatitis-SI: 13 patients, lipase output < 10% normal values and pancreolauryl test < 20%), those with only mild insufficiency (chronic pancreatitis-MI: seven patients), and those with normal secretion (chronic pancreatitis-NF: eight patients). The chronic pancreatitis-SI patients present significantly greater gastric acidification in the postprandial periods compared with controls (P1: p < 0.001; P2: p < 0.01), and with chronic pancreatitis-MI plus chronic pancreatitis-NF subjects (P1: p < 0.01; P2: p < 0.05), taken together. In conclusion, gastric acidity, exocrine pancreatic insufficiency, and impaired digestion are closely related during the course of chronic pancreatitis.